Diffusion and influence of Cu on properties of CdTe thin films and CdTe/CdS cells - Dzhafarov, TD; Yesilkaya, SS; Canli, NY; Caliskan, M (ELSEVIER, 2005)
The effective diffusion coefficients of Cu for thermal and photodiffusion in the CdTe films have been estimated from resistivity versus duration of thermal or photoannealing curves. In the temperature range 60-200degreesC the effective coefficient of thermal diffusion (D) and photodiffusion (D-ph) are described as D-t = 7.3 x 10(-7)exp(-0.33/kT) and D-ph = 4.7 x 10(-8)exp(-0.20/kT). It is found that the diffusion doping of CdTe thin films by Cu at 400degreesC results in a sharp decrease of resistivity up to 7 orders of magnitude of p-type material, depending on thickness of Cu film. The comparative study of performance of CdTe(Cu)/CdS and CdTe/CdS cells has been studied. It is shown that the diffusion doping of CdTe film by Cu increases efficiency of CdTe(Cu)/CdS cells from 0.9% to 6.8%. The degradation of photovoltaic parameters of CdTe(Cu)/CdS cell, during testing under forward and reverse bias at room temperature, proceeds at a larger rate than those of CdTe/CdS cell without Cu. The degradation of performance of CdTe(Cu)/CdS cells is tentatively assigned to electrodiffusion of Cu in CdTe, resulting in redistribution of concentration of Cu-related centers in CdTe film and heterojunction region. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdTe cell; Cu; diffusion; degradation; SOLAR-CELLS; DOPED CDTE; AG; STABILITY; Energy & Fuels; Materials Science; Physics